Self-Defense Mechanism of The Main Character in Ottessa Moshfegh’s Novel My Year of Rest and Relaxation (An Analysis of Freud’s Psychoanalysis) - Agustiyani Agustiyani Agustiyani (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2016)
This study aimed to analyze the self-defense mechanism of the main character in the novel My Year of Rest and Relaxation by Ottessa Moshfegh. This study was conducted using descriptive qualitative method. Some of the theories applied were those of Freud’s namely psychoanalysis, concept of anxiety, and defense mechanism. The data was collected from the novel My Year of Rest and Relaxation by Ottessa Moshfegh as the primary source of data, while the secondary source of data is articles and books that are related to theories used. Data was collected through reading, identifying, annotating, and organizing. In analyzing the data, the researcher conducted several steps. First, the researcher presented the data in the form of text. Second, the researcher described the text. Third, the researchers interpreted the data by making more elaborated descriptions of the data and its relation with the theories used. Last, the researcher provided conclusion that summarizes the findings. The results of the study showed that there is an imbalance in the main character’s personality, in which her ego cannot mediate the conflicts between her urge (the id) and the moral principle (superego). This imbalance causes the main character to experience neurotic anxieties on the daily. To reduce the anxiety, the main character performs several self-defense mechanisms that are shown in several types namely rationalization, denial, repression, regression, reaction formation, projection, displacement, and sublimation.